Character Education Thought of Soefyan Abdul Wahab: A Philological Approach, Critical Discourse Analysis, and Practical Implications at Pesantren Matholiul Anwar - Al-Ali, Sinta C. (Yayasan Al-Aziziyah Tlogoagung Kedungadem Bojonegoro, 2025)
This research is motivated by the urgent need to strengthen character education in response to the ongoing moral crisis in Indonesian society. The study focuses on KH. Soefyan Abdul Wahab's concept of character education as presented in the manuscript Pesan Hidup Sehari-hari. Employing an ekstem philological approach combined with critical discourse analysis, the research aims not only to restore the text but also to reveal the ideological and social dimensions underlying the narrative. Using qualitative library-based methods and semi-structured interviews for triangulation, data analysis follows stages of inventory, description, transliteration, text criticism, and discourse interpretation based on Fairclough’s CDA model. Findings demonstrate that KH. Soefyan’s character education integrates religious values, moral exemplarity, and social actualization, centered on sincerity, responsibility, independence, mutual cooperation, and integrity. The manuscript holds both historical value and contemporary pedagogical relevance as a contextual model for character education. The study’s limitation lies in focusing on a single manuscript, suggesting future comparative research with other pesantren texts and digitization initiatives to develop alternative educational resources.